Association of Plasma Level of TNF-Related Apoptosis-Inducing Ligand with Severity and Outcome of Sepsis - Yoo, Hongseok (J Clin Med, 2020)
Recent studies have suggested that TNF-related apoptosis-inducing ligand (TRAIL) is associated with mortality in sepsis, possibly through necroptosis. The objective of this study was to analyze the association between the plasma level of TRAIL and sepsis severity and outcomes. Furthermore, the plasma level of TRAIL was compared to that of receptor-interacting protein kinase-3 (RIPK3), a key executor of necroptosis, to identify any correlation between TRAIL and necroptosis. Plasma levels of TRAIL and RIPK3 from consecutively enrolled critically ill patients were measured by ELISA. Of 190 study patients, 59 (31.1%) and 84 (44.2%) patients were diagnosed with sepsis and septic shock, respectively. There was a trend of decreased plasma level of TRAIL across the control, sepsis, and septic shock groups. For 143 patients with sepsis, patients with low plasma TRAIL were more likely to have septic shock and higher SAPS3 and SOFA scores. However, no difference in 28-day and 90-day mortalities was observed between the two groups. The plasma level of TRAIL was inversely associated with RIPK3 in patients with sepsis. Plasma levels of TRAIL increased over time on days three and seven, and were inversely associated with sepsis severity and RIPK3 level, but not with mortality.